A Digital Twin for a World Heritage Destination - Sampaio de Almeida, D.; Brito e Abreu, F.; Boavida-Portugal, I. (2025 IEEE Smart World Congress (SWC), 2026)
Sintra, a UNESCO World Heritage Site, is one of Portugal's most popular tourist destinations. However, as a historical urban center, it suffers from its success: overcrowding and traffic bottlenecks. Digital Twins (DT) have proven instrumental in monitoring, predicting, and prescribing improvement actions to mitigate the effects of these phenomena. We present an in-development DT system designed to manage traffic and overcrowding scenarios in this town, which can be applied to other analogous heritage sites. The DT overall planned architecture, principal components, primary data sources to feed the system, envisioned simulation techniques, human-machine interfaces, main functionalities and purposes, and an initial prototype for destination management organisations are presented.